Hadis Meluruskan Saf Salat: Dari Pendekatan Kritis ke Persoalan Fisiologis-Psikologis - 'Aziizah, 'Aabidah Ummu (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The background of this research stems from the many understanding of the hadith to straighten out this saf of prayer which ultimately leads to divisions among Muslims. This is characterized by a variety of sadistic substance alignment of saf that explicitly looks different, there are hadiths that indicate threats and some indicate utility. But on the other hand as Muslims, belief in the source of Islamic law in the form of al-Quran and as-Sunnah is a mandatory consequence. This research method uses qualitative research with a library study approach (library research) and is descriptive and applied Musahadi Ham's takhrij and ma'anil methods of the hadith include historical criticism, eiditis criticism and praxis criticism. The results of this study indicate that the alignment of the salat saf which means to correct all differences in one unit. saf line frame has no relationship with attachment between several limbs from one mushalli to another. This spirit is proven through physiology and psychology research which proves that someone in the regularity of the series of prayers will can deliver his on significant physical relaxation and prevention from various diseases.